Strategi Pemasaran dalam Meningkatkan Kredibilitas Tenun Leny Bumpak melalui Bazar - Sari, Nadia Yupita; Fauziah, Dzamratul; Yuneri, Winda; Zaki, Khozin; Indra, Yetti Afrida (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to analyze the role of the bazaar as a strategic means in increasing the credibility of Leny Bumpak Batik Weaving as a leading local product. In the face of increasingly fierce market competition, MSMEs need to build consumer trust through effective promotional media. The bazaar was chosen as the main medium because it provides opportunities for direct interaction with consumers, introducing products widely, and building a positive brand image. This study uses a descriptive qualitative method with data collection techniques through observation, in-depth interviews, and documentation. The results show that active participation in the bazaar significantly increases public trust in product quality, expands customer networks, and strengthens brand positioning in the local market. This research recommends that MSMEs make the bazaar an integral part of their long-term marketing strategy.